A new species of Pachytrechodes Jeannel, 1960 (Coleoptera: Carabidae: Trechinae) from Tanzania, with a key to species - Belousov, Igor A.; Nyundo, Bruno A. (Zootaxa, 2013)
Pachytrechodes brevis Belousov & Nyundo, new species, is described from the Udzungwa Mountains, Tanzania. This species is the first member of the genus found outside of the Uluguru Mountains. A key to the four currently known species of Pachytrechodes is included, based on Uéno’s (1987) key. The distribution of all species is mapped.